Market selection in large economies: A matter of luck - Filippo Massari (Theoretical Economics, 2019)
In a general equilibrium model with a continuum of traders and bounded aggregate endowment, I investigate the Market Selection Hypothesis that markets favor traders with accurate beliefs. Contrary to known results for economies with (only) finitely many traders, I find that risk attitudes affect traders' survival and that markets can favor 'lucky' traders with incorrect beliefs over 'skilled' traders with accurate beliefs. My model allows for a clear distinction between luck and skills and it shows that market selection forces induce efficient prices even when accurate traders do not survive in the long run.
Keywords: D50; D90; G12; 330; Market selection hypothesis; asset pricing; general equilibrium